Prevention of eating disorders and obesity: experience report of implementation of the program New Moves - Dunker, Karin Louise Lenz (2018)
The aim of this study was to reflect upon the adaptation process, difficulties and potentials of the implementation of the New Moves program, designed to prevent obesity and eating disorders in girls of public schools in São Paulo (SP). The Brazilian version of the program has the potential to use effective behavioral techniques such as socio-cognitive theory and motivational interviewing, and present a content that addresses factors common to obesity and eating disorders, which can be applied considering the difficulties related to adaptation process and implementation presented in the study.